Perfluoropolyether-based magnetic liquid with low viscosity and high stability and preparation method thereof

The composite nanomagnetic particles of iron trioxide and carbon nanotubes prepared by chemical precipitation in perfluoropolyether-based carrier liquid and surfactant modification are solved by the low viscosity of perfluoropolyether-based magnetic liquid. The problem of poor stability of magnetic field dispersion has achieved stable performance improvement under high-speed sealing conditions.

CN119517593APending Publication Date: 2025-02-25SICHUAN ZHAOQIANG TITANIUM MAGNETIC TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411625263.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing perfluoropolyether-based magnetic liquid has poor magnetic field dispersion stability at low viscosity, resulting in overheating problems under high-speed sealing conditions.

Method used

Chemical precipitation method is used to prepare composite nanomagnetic particles of iron trioxide and carbon nanotubes, and under the modification of perfluoropolyether surfactant, the particles are stably dispersed in perfluoropolyether-based carrier liquid to improve the magnetic liquid dispersion stability and magnetic field stability.

Benefits of technology

Under the low solid content, the dispersion stability and magnetic field stability of magnetic liquid are significantly improved, and the overheating problem of high viscosity magnetic liquids is solved in the use of high-speed sealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517593A_ABST
    Figure CN119517593A_ABST
Patent Text Reader

Abstract

The invention discloses a low-viscosity high-stability perfluoropolyether-based magnetic liquid and a preparation method thereof, and relates to the technical field of magnetic material preparation, and the preparation method comprises the following steps: preparing composite nano magnetic particles of ferroferric oxide and carbon nanotubes by adopting a chemical in-situ coprecipitation method; coating the composite nano magnetic particles with a perfluoropolyether surfactant; the composite nano magnetic particles are dispersed into the perfluoropolyether oil-based carrier liquid, and the solid content of the composite nano magnetic particles accounts for 5 wt%-20 wt%. Ferroferric oxide and carbon nano tube composite nano magnetic particles are obtained through a chemical precipitation method, the particles are stably dispersed in perfluoropolyether-based carrier liquid under the modification effect of a surfactant, and under the condition of low solid content, the dispersion stability and magnetic field stability of the magnetic liquid are greatly improved; the problem of overheating caused by the fact that high-viscosity magnetic liquid is used for high-rotating-speed sealing is greatly solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic material preparation, and in particular to a low-viscosity and high-stability perfluoropolyether-based magnetic liquid and a preparation method thereof. Background Art

[0002] Magnetic liquid belongs to a type of magnetic fluid material, and its characteristic is that the size of the magnetic particles contained in it is about 10nm. Magnetic liquid is a highly stable colloidal solution composed of nanomagnetic particles, modifiers, and base carrier liquid. Due to the presence of nanomagnetic particles and base carrier liquid, magnetic liquid has both magnetism and fluidity in a magnetic field environment, and different base carrier liquids have different performance properties, which makes the magnetic liquid meet the use of various working conditions such as high and low temperature, alkali corrosion resistance, high and low speed, etc. Therefore, magnetic liquid is a new type of functional nanomagnetic material, which has received extensive attention in lubrication, speakers, medicine, automotive damping, sealing and other industries.

[0003] With the increasing attention paid to magnetic fluid research, the preparation and performance of magnetic fluids with different carrier fluids have basically matured. They have been rapidly developed and applied in different industries, especially in the sealing industry, which has gradually solved the problems of poor sealing effect and inability to seal in traditional mechanical seals. With the continuous expansion of the application scope of magnetic fluids in the sealing industry, some conventional silicone oil-based, ester-based, and kerosene-based magnetic fluids can no longer meet the requirements. Fluoroether oil-based magnetic fluids can solve the sealing problem in harsh environments because of the good chemical inertness and high and low temperature resistance of their carrier fluids.

[0004] At present, there are few types of perfluoropolyether products at home and abroad, and it is difficult to obtain perfluoropolyether surfactants with stable quality with current technology. Therefore, it is difficult for modified nano-magnetic particles to be stably dispersed in perfluoropolyether oil in an ideal way. The instability is magnified when the solid content of the magnetic liquid is extremely low, which ultimately reduces the magnetic field dispersion stability of the magnetic liquid, thus affecting its use. Under high-speed sealing conditions, the higher the viscosity of the magnetic liquid, the more friction heat will be generated at the contact part, thus affecting the performance of the magnetic liquid. Therefore, the viscosity of the magnetic liquid needs to be as low as possible. Summary of the invention

[0005] Based on the problem that the magnetic field dispersion stability of perfluoropolyether-based magnetic liquid is poor at low viscosity due to the uneven performance of perfluoropolyether surfactants at home and abroad, the purpose of the present invention is to provide a low-viscosity and high-stability perfluoropolyether-based magnetic liquid and a preparation method thereof, and to obtain ferroferric oxide and carbon nanotube composite nanomagnetic particles by chemical precipitation method, and under the modification of surfactant, the particles are stably dispersed in the perfluoropolyether-based carrier liquid, and under the condition of low solid content, the dispersion stability and magnetic field stability of the magnetic liquid are greatly improved, which greatly improves the overheating problem existing in high-speed sealing using high-viscosity magnetic liquid.

[0006] The present invention is achieved through the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid, comprising the following steps:

[0008] In the first stage, the composite nano-magnetic particles of ferroferric oxide and carbon nanotubes were prepared by chemical in-situ co-precipitation method;

[0009] In the second stage, the composite nanomagnetic particles are coated with a perfluoropolyether surfactant;

[0010] In the third stage, the composite nano-magnetic particles coated with a perfluoropolyether surfactant are dispersed in a perfluoropolyether oil-based carrier liquid, wherein the solid content of the composite nano-magnetic particles is 5 wt % to 20 wt %.

[0011] In some specific embodiments, during the dispersion stage, the solid content of the composite nano-magnetic particles can be 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt% and the like.

[0012] Furthermore, the weight ratio of the carbon nanotubes to the ferrosoferric oxide is 0.5wt% to 1wt%; the weight ratio of the perfluoropolyether surfactant to the ferrosoferric oxide is 30wt% to 50wt%.

[0013] In some specific embodiments, the weight ratio of carbon nanotubes to ferrosoferric oxide can be 0.5wt%, 0.56wt%, 0.62wt%, 0.68wt%, 0.75wt%, 0.78wt%, 0.84wt%, 0.88wt%, 0.95wt%, 1wt%, etc.

[0014] In the particle coating stage, the weight ratio of the surfactant to the ferrosoferric oxide particles can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc.

[0015] Furthermore, the specific method for preparing the nano-magnetic particles of ferroferric oxide and carbon nanotubes composite by chemical in-situ coprecipitation method comprises the following steps:

[0016] The carbon nanotubes are added into anhydrous ethanol and subjected to ultrasonic treatment to obtain a carbon nanotube dispersion solution;

[0017] Weighing a ferric salt and a ferrous salt to obtain an iron salt reaction precursor solution;

[0018] The iron salt precursor solution is added into the stirred carbon nanotube solution, and the alkali is added to start the reaction. After the reaction is completed, the composite nano-magnetic particles are washed with water, dried and ground.

[0019] Furthermore, the molar ratio of the ferric iron salt to the ferrous iron salt is (1.5-1.8):1, and the concentration of the ferric iron in the reaction system is 0.2-0.6 mol / L.

[0020] In some specific embodiments, the molar ratio of the ferric salt to the ferrous salt can be 1.5:1, 1.6:1, 1.7:1, 1.8:1, etc.

[0021] The concentration of ferric iron in the reaction system can be 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, 0.55 mol / L, 0.6 mol / L, etc.

[0022] In some specific embodiments, the trivalent iron salt includes FeCl3·6H2O; the divalent iron salt includes FeSO4·7H2O.

[0023] Furthermore, when the composite nano-magnetic particles of ferroferric oxide and carbon nanotubes are prepared by chemical in-situ co-precipitation method, the reaction pH value is 10-12 and the reaction time is 30-60 minutes.

[0024] In some specific embodiments, the reaction pH value when preparing the composite nano-magnetic particles of ferroferric oxide and carbon nanotubes by chemical in-situ coprecipitation method can be 10, 10.5, 11, 11.5, 12, etc. The reaction time can be 30 min, 40 min, 50 min, 60 min, etc.

[0025] Furthermore, the average diameter of the carbon nanotubes is 10-15 nm, and the length is 3-12 um.

[0026] Among them, in some specific embodiments, the average tube diameter of the carbon nanotubes can be 10nm, 11nm, 12nm, 13nm, 14nm, 15nm, etc., and the length can be 3um, 4um, 5um, 6um, 7um, 8um, 9um, 10um, 11um, 12um, etc.

[0027] Furthermore, the perfluoropolyether surfactant includes perfluoropolyether carboxylic acid.

[0028] Furthermore, the reaction temperature for preparing the composite nanotube magnetic particles is 50°C to 80°C.

[0029] In some specific embodiments, the reaction temperature for preparing composite nanotube magnetic particles can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0030] Furthermore, before coating the composite nano-magnetic particles, the pH value of the reaction system is adjusted to 5-7, and the reaction time is 2-6 hours.

[0031] In some specific embodiments, before coating the composite nanomagnetic particles, the pH value of the reaction system is adjusted to 5, 5.5, 6, 6.5, 7, etc., and the reaction time is 2 to 6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, etc.

[0032] In a second aspect, the present application provides a low-viscosity and high-stability perfluoropolyether-based magnetic liquid prepared by the above-mentioned preparation method.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0034] (1) The present invention uses a chemical precipitation method to obtain ferroferric oxide and carbon nanotube composite nanomagnetic particles, and under the modification of a surfactant, the particles are stably dispersed in a perfluoropolyether-based carrier liquid. Under the condition of low solid content, the dispersion stability and magnetic field stability of the magnetic liquid are greatly improved, which greatly improves the overheating problem existing in high-speed sealing using high-viscosity magnetic liquids.

[0035] (2) In the preparation method of the present invention, the carbon nanotubes used in the preparation of composite nano-magnetic particles of ferroferric oxide and carbon nanotubes by a chemical in-situ co-precipitation method have a large specific surface area and a small density, which has the effect of improving the dispersion stability of the system in the colloidal solution of the magnetic liquid. Moreover, the large specific surface area of ​​the carbon nanotubes makes them have good adsorption capacity, so that ferroferric oxide particles are generated on their surface. In addition, the carbon nanotubes themselves are easy to form a spatial network structure, which can play a role in slowing down the sedimentation of nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0037] Figure 1 is the rheological diagram of the magnetic liquid prepared in Example 1 of the present invention;

[0038] Figure 2 is a VSM diagram of the magnetic liquid prepared in Example 1 of the present invention;

[0039] Figure 3 is a SEM image of the magnetic liquid prepared in Example 1 of the present invention;

[0040] Figure 4 is the rheological diagram of the magnetic liquid prepared in Example 2 of the present invention;

[0041] Figure 5 is a VSM diagram of the magnetic liquid prepared in Example 2 of the present invention;

[0042] Figure 6 is a SEM image of the magnetic liquid prepared in Example 2 of the present invention;

[0043] Figure 7 is the rheological diagram of the magnetic liquid prepared in Example 3 of the present invention;

[0044] Figure 8 is a VSM diagram of the magnetic liquid prepared in Example 3 of the present invention;

[0045] Fig. 9 is a SEM image of the magnetic liquid prepared in Example 3 of the present invention;

[0046] Fig.10 is the rheological diagram of the magnetic liquid prepared in Example 4 of the present invention;

[0047] Fig.11 is a VSM diagram of the magnetic liquid prepared in Example 4 of the present invention;

[0048] Fig.12 is a SEM image of the magnetic liquid prepared in Example 4 of the present invention;

[0049] Fig.13 is the rheological diagram of the magnetic liquid prepared in Example 5 of the present invention;

[0050] Fig.14 is a VSM diagram of the magnetic liquid prepared in Example 5 of the present invention;

[0051] Fig.15 This is a SEM image of the magnetic liquid prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0052] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0053] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] This embodiment provides a method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid. The perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles, perfluoropolyether carboxylic acid, and perfluoropolyether oil, with a particle solid content of 8 wt%.

[0056] The specific preparation method is:

[0057] S1. Weigh 0.048 g of carbon nanotubes into a 50 mL beaker, add 30 mL of anhydrous ethanol, and transfer the dispersed carbon nanotube solution to a reaction vessel after ultrasonic treatment at room temperature for 30 min, and continue mechanical stirring for 10 min.

[0058] S2. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0059] S3. Add 10% by volume dilute hydrochloric acid into the reaction container until the pH value of the reaction system is 7, add 1.63 g of perfluoropolyether carboxylic acid into the reaction system, maintain the temperature and speed for 3 hours, and after the reaction, wash the particles 10 times, dry for 10 hours, and grind to obtain iron oxide carbon nanotube composite nanomagnetic particles.

[0060] S4. Add the composite nano-magnetic particles obtained in S3 into 62.68 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0061] The rheological properties, saturation magnetization intensity and particle size morphology of the perfluoropolyether-based magnetic liquid in this embodiment were tested, respectively. Figure 1 , Figure 2 , Figure 3 As shown. Figure 1 It can be seen from the above that the magnetic liquid prepared in this embodiment has a low viscosity, which can be as low as 256.92 mPa·s. Figure 2 It can be seen that the magnetic liquid prepared in this embodiment has a low viscosity and ensures an applicable saturation magnetization of 8.78emu / g. Figure 3 It can be seen that the ferroferric oxide particles in the magnetic liquid prepared in this embodiment have a complete morphology, a particle size of 10-20 nm, and the ferroferric oxide nucleates and grows around the carbon nanotubes, and the carbon nanotubes also interact with each other to form a network structure. In addition, the magnetic liquid prepared in this embodiment can be stably dispersed for a long time in a non-magnetic field environment, and can also exist stably for a long time in a magnetic field environment.

[0062] Example 2

[0063] This embodiment provides a method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid. The perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles, perfluoropolyether carboxylic acid, and perfluoropolyether oil, with a particle solid content of 10 wt%.

[0064] S1. Weigh 0.043 g of carbon nanotubes into a 50 mL beaker, add 30 mL of anhydrous ethanol, and transfer the dispersed carbon nanotube solution to a reaction vessel after ultrasonic treatment at room temperature for 30 min, and continue mechanical stirring for 10 min.

[0065] S2. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0066] S3. Add 10% by volume dilute hydrochloric acid into the reaction container until the pH value of the reaction system is 7, add 1.63 g of perfluoropolyether carboxylic acid into the reaction system, maintain the temperature and speed for 3 hours, and after the reaction, wash the particles 10 times, dry for 10 hours, and grind to obtain iron oxide carbon nanotube composite nanomagnetic particles.

[0067] S4. Add the composite nano-magnetic particles obtained in S3 into 49.05 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0068] The rheological properties, saturation magnetization intensity and particle size morphology of the perfluoropolyether-based magnetic liquid in this embodiment were tested, respectively. Figure 3 , Figure 4 , Figure 5 As shown. Figure 3 It can be seen from the above that the magnetic liquid prepared in this embodiment has a low viscosity, which can be as low as 287.49 mPa·s. Figure 4 It can be seen that the magnetic liquid prepared in this embodiment has a low viscosity and ensures an applicable saturation magnetization of 9.58emu / g. Figure 5 It can be seen that the ferroferric oxide particles in the magnetic liquid prepared in this embodiment have a complete morphology, a particle size of 10-20 nm, and the ferroferric oxide nucleates and grows around the carbon nanotubes, and the carbon nanotubes also interact with each other to form a network structure. In addition, the magnetic liquid prepared in this embodiment can be stably dispersed for a long time in a non-magnetic field environment, and can also exist stably for a long time in a magnetic field environment.

[0069] Example 3

[0070] This embodiment provides a method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid. The perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles, perfluoropolyether carboxylic acid, and perfluoropolyether oil, with a particle solid content of 12 wt%.

[0071] S1. Weigh 0.037 g of carbon nanotubes into a 50 mL beaker, add 30 mL of anhydrous ethanol, and transfer the dispersed carbon nanotube solution to a reaction vessel after ultrasonic treatment at room temperature for 30 min, and continue mechanical stirring for 10 min.

[0072] S2. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0073] S3. Add 10% by volume dilute hydrochloric acid into the reaction container until the pH value of the reaction system is 7, add 1.63 g of perfluoropolyether carboxylic acid into the reaction system, maintain the temperature and speed for 3 hours, and after the reaction, wash the particles 10 times, dry for 10 hours, and grind to obtain iron oxide carbon nanotube composite nanomagnetic particles.

[0074] S4. Add the composite nano-magnetic particles obtained in S3 into 39.97 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0075] The rheological properties, saturation magnetization intensity and particle size morphology of the perfluoropolyether-based magnetic liquid in this embodiment were tested, respectively. Figure 7 , Figure 8 , Fig. 9 As shown. Figure 7 It can be seen from the above that the magnetic liquid prepared in this embodiment has a low viscosity, which can be as low as 299.20 mPa·s. Figure 8 It can be seen that the magnetic liquid prepared in this embodiment has a low viscosity and ensures an applicable saturation magnetization of 10.60emu / g. Fig. 9 It can be seen that the ferroferric oxide particles in the magnetic liquid prepared in this embodiment have a complete morphology, a particle size of 10-20 nm, and the ferroferric oxide nucleates and grows around the carbon nanotubes, and the carbon nanotubes also interact with each other to form a network structure. In addition, the magnetic liquid prepared in this embodiment can be stably dispersed for a long time in a non-magnetic field environment, and can also exist stably for a long time in a magnetic field environment.

[0076] Example 4

[0077] This embodiment provides a method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid. The perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles, perfluoropolyether carboxylic acid, and perfluoropolyether oil, with a particle solid content of 5wt%.

[0078] S1. Weigh 0.055 g of carbon nanotubes into a 50 mL beaker, add 30 mL of anhydrous ethanol, and transfer the dispersed carbon nanotube solution to a reaction vessel after ultrasonic treatment at room temperature for 30 min, and continue mechanical stirring for 10 min.

[0079] S2. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0080] S3. Add 10% by volume dilute hydrochloric acid into the reaction container until the pH value of the reaction system is 7, add 1.63 g of perfluoropolyether carboxylic acid into the reaction system, maintain the temperature and speed for 3 hours, and after the reaction, wash the particles 10 times, dry for 10 hours, and grind to obtain iron oxide carbon nanotube composite nanomagnetic particles.

[0081] S4. Add the composite nano-magnetic particles obtained in S3 into 103.55 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0082] The rheological properties, saturation magnetization intensity and particle size morphology of the perfluoropolyether-based magnetic liquid in this embodiment were tested, respectively. Fig.10 , Fig.11 , Fig.12 As shown. Fig.10 It can be seen from the above that the magnetic liquid prepared in this embodiment has a low viscosity, which can be as low as 224.72 mPa·s. Fig.11 It can be seen that the magnetic liquid prepared in this embodiment has a low viscosity and ensures an applicable saturation magnetization intensity of 7.32emu / g. Fig.12 It can be seen that the ferroferric oxide particles in the magnetic liquid prepared in this embodiment have a complete morphology, a particle size of 10-20 nm, and the ferroferric oxide nucleates and grows around the carbon nanotubes, and the carbon nanotubes also interact with each other to form a network structure. In addition, the magnetic liquid prepared in this embodiment can be stably dispersed for a long time in a non-magnetic field environment, and can also exist stably for a long time in a magnetic field environment.

[0083] Example 5

[0084] This embodiment provides a method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid. The perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles, perfluoropolyether carboxylic acid, and perfluoropolyether oil, with a particle solid content of 20 wt%.

[0085] S1. Weigh 0.027 g of carbon nanotubes into a 50 mL beaker, add 30 mL of anhydrous ethanol, and transfer the dispersed carbon nanotube solution to a reaction vessel after ultrasonic treatment at room temperature for 30 min, and continue mechanical stirring for 10 min.

[0086] S2. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0087] S3. Add 10% by volume dilute hydrochloric acid into the reaction container until the pH value of the reaction system is 7, add 1.63 g of perfluoropolyether carboxylic acid into the reaction system, maintain the temperature and speed for 3 hours, and after the reaction, wash the particles 10 times, dry for 10 hours, and grind to obtain iron oxide carbon nanotube composite nanomagnetic particles.

[0088] S4. Add the composite nano-magnetic particles obtained in S3 into 21.80 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0089] The rheological properties, saturation magnetization intensity and particle size morphology of the perfluoropolyether-based magnetic liquid in this embodiment were tested, respectively. Fig.13 , Fig.14 , Fig.15 As shown. Fig.13 It can be seen from the above that the magnetic liquid prepared in this embodiment has a low viscosity, which can be as low as 387.47 mPa·s. Fig.14 It can be seen that the magnetic liquid prepared in this embodiment has a low viscosity and ensures an applicable saturation magnetization of 14.40emu / g. Fig.15 It can be seen that the ferroferric oxide particles in the magnetic liquid prepared in this embodiment have a complete morphology, a particle size of 10-20 nm, and the ferroferric oxide nucleates and grows around the carbon nanotubes, and the carbon nanotubes also interact with each other to form a network structure. In addition, the magnetic liquid prepared in this embodiment can be stably dispersed for a long time in a non-magnetic field environment, and can also exist stably for a long time in a magnetic field environment.

[0090] Comparative Example 1

[0091] This comparative example is a method for preparing a perfluoropolyether-based magnetic liquid, wherein the perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles and perfluoropolyether oil, with a particle solid content of 8 wt%. Different from Example 1, the perfluoropolyether carboxylic acid is not used to modify the composite nanomagnetic particles in this comparative example.

[0092] The specific preparation method is:

[0093] S1. Weigh 0.048 g of carbon nanotubes into a 50 mL beaker, add 30 mL of anhydrous ethanol, and transfer the dispersed carbon nanotube solution to a reaction vessel after ultrasonic treatment at room temperature for 30 min, and continue mechanical stirring for 10 min.

[0094] S2. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0095] S3. After the reaction is completed, the particles are washed 10 times with water, dried for 10 hours, and ground to obtain Fe3O4 carbon nanotube composite nanomagnetic particles.

[0096] S4. Add the composite nano-magnetic particles obtained in S3 into 62.68 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0097] The stability of the perfluoropolyether-based magnetic liquid in this comparative example was observed, and it was found that the dispersion stability of the composite nano-magnetic particles not modified with perfluoropolyether carboxylic acid in the perfluoropolyether oil was extremely poor, and obvious phase separation of particles and perfluoropolyether oil occurred in the magnetic liquid, indicating that in the absence of the joint action of perfluoropolyether carboxylic acid, the composite nano-magnetic particles could not independently achieve stable dispersion in the perfluoropolyether oil.

[0098] Comparative Example 2

[0099] The comparative example is a method for preparing a perfluoropolyether-based magnetic liquid, wherein the perfluoropolyether-based magnetic liquid is prepared from ferroferric oxide carbon nanotube composite nanomagnetic particles and perfluoropolyether oil, with a particle solid content of 8 wt%. Different from Example 1, the ferroferric oxide carbon nanotube composite nanomagnetic particles in the comparative example are replaced by ferroferric oxide nanoparticles.

[0100] The specific preparation method is:

[0101] S1. Weigh 10.81g of FeCl3·6H2O and 6.54g of FeSO4·7H2O in a beaker, prepare 100mL of iron salt reaction precursor solution, stir evenly and transfer to the reaction vessel. Weigh 7.53g of NaOH in a beaker, prepare 100mL of strong alkaline solution, stir evenly and add to the reaction vessel, maintain the reaction temperature at 60°C, the reaction speed at 600r / min, and the reaction time at 60min.

[0102] S2. Add 10% volume fraction of dilute hydrochloric acid into the reaction container until the pH value of the reaction system is 7, add 1.63g of perfluoropolyether carboxylic acid into the reaction system, maintain the temperature and speed for 3h, and after the reaction, wash the particles 10 times, dry for 10h, and grind to obtain ferrosoferric oxide nanoparticles.

[0103] S3. Add the ferrosoferric oxide nanoparticles obtained in S2 to 62.68 g of perfluoropolyether oil, and stir mechanically at 600 r / min for 10 h to finally obtain a perfluoropolyether-based magnetic liquid.

[0104] The stability of the perfluoropolyether-based magnetic liquid in this comparative example was observed, and it was found that the magnetic liquid could be stably dispersed in the absence of a magnetic field, but could not be stably dispersed in the presence of a magnetic field. After being placed in a magnetic field for a long time, the magnetic liquid was observed to have obvious upper and lower stratification when the magnetic field was removed, and could not be restored to a uniform fluid state, indicating that without the combined action of carbon nanotubes, the ferroferric oxide nanoparticles could not be stably dispersed in the perfluoropolyether oil at a low solid content ratio.

[0105] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid, characterized in that: The following steps are involved: In the first stage, the composite nano-magnetic particles of ferroferric oxide and carbon nanotubes were prepared by chemical in-situ co-precipitation method; In the second stage, the composite nanomagnetic particles are coated with a perfluoropolyether surfactant; In the third stage, the composite nano-magnetic particles coated with a perfluoropolyether surfactant are dispersed in a perfluoropolyether oil-based carrier liquid, wherein the solid content of the composite nano-magnetic particles is 5 wt % to 20 wt %.

2. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The weight ratio of the carbon nanotubes to the ferrosoferric oxide is 0.5 wt% to 1 wt%; the weight ratio of the perfluoropolyether surfactant to the ferrosoferric oxide is 30 wt% to 50 wt%.

3. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The specific method for preparing nano-magnetic particles composited with ferroferric oxide and carbon nanotubes by chemical in-situ coprecipitation method comprises the following steps: The carbon nanotubes are added into anhydrous ethanol and subjected to ultrasonic treatment to obtain a carbon nanotube dispersion solution; Weighing a trivalent iron salt and a divalent iron salt to obtain an iron salt reaction precursor solution; The iron salt precursor solution is added to the stirred carbon nanotube solution, and the alkali is added to start the reaction. After the reaction is completed, the composite nano-magnetic particles are washed with water, dried, and ground.

4. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 3, characterized in that: The molar ratio of the ferric iron salt to the ferrous iron salt is (1.5-1.8):1, and the concentration of the ferric iron in the reaction system is 0.2-0.6 mol / L.

5. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: When the composite nano-magnetic particles of ferroferric oxide and carbon nanotubes are prepared by chemical in-situ coprecipitation method, the reaction pH value is 10-12 and the reaction time is 30-60 minutes.

6. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The average diameter of the carbon nanotubes is 10-15 nm, and the length is 3-12 μm.

7. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The perfluoropolyether surfactant includes perfluoropolyether carboxylic acid.

8. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: The reaction temperature for preparing composite nanotube magnetic particles is 50°C to 80°C.

9. The method for preparing a low-viscosity and high-stability perfluoropolyether-based magnetic liquid according to claim 1, characterized in that: Before coating the composite nano-magnetic particles, the pH value of the reaction system is adjusted to 5-7, and the reaction time is 2-6 hours.

10. A low-viscosity and high-stability perfluoropolyether-based magnetic liquid, characterized in that: The preparation method is described in any one of claims 1 to 9.

Citation Information

Cited By

  • High-stability magnetic liquid and preparation method thereof

    CN120613204A